Lithium ion secondary battery
By adjusting the content of element Si in the negative electrode active material and the average spherical degree of silicon-carbon material and matching the appropriate ternary materials, the problem of failure of high-nickel ternary positive electrode and silicon-carbon negative electrode system batteries during the cycle process is solved, and the circulation performance and safety of the battery are improved.
Patent Information
- Application Number
- CN202411916879.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
Existing high-nickel ternary positive electrode and silicon-carbon negative electrode system batteries are prone to failure during the cycle, resulting in rapid attenuation of the circulation capacity and serious safety problems such as battery deformation, short circuit, fire and explosion.
By adjusting the content of element Si in the negative electrode active material and the average spherical degree of silicon-carbon material, matching the ternary material with a molar content of appropriate element Ni, the content of transition metal ions deposited to the negative electrode is controlled, thereby improving the stability of the SEI film generated on the surface of silicon-carbon material.
It effectively avoids the phenomenon of lithium plating and the formation of lithium dendrites, solves the failure and safety problems of the battery during the circulation process, and improves the circulation performance and service life of the battery.
Smart Images

Figure CN119725682A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a lithium-ion secondary battery. Background Art
[0002] In order to further improve the energy density of batteries, high nickel ternary positive electrode (NCM, Ni molar content of 0.65-0.95) and silicon carbon (Si / C) negative electrode with high gram capacity have gradually received widespread attention and use. However, compared with carbon-based negative electrode, silicon carbon material has poor conductivity and large expansion, which will deteriorate the battery cycle performance to a certain extent. In addition, the solid electrolyte membrane (SEI membrane) generated on the surface of silicon carbon negative electrode is easily affected by the transition metal ions dissolved from the positive electrode, which will not only cause lithium plating on the surface of silicon carbon (i.e., lithium ions are deposited on the surface of the negative electrode), accelerate the failure of the battery, and make its cycle capacity decay rapidly; and as the lithium dendrites grow, the diaphragm is punctured, and eventually the battery will have serious safety problems such as appearance deformation, short circuit, fire and explosion, especially at a high silicon carbon mixing ratio. The risk of failure will increase sharply. Therefore, how to avoid the failure of batteries with high nickel ternary and high silicon carbon-based material systems during the cycle process is one of the key issues in promoting their commercialization. Summary of the invention
[0003] The purpose of the present invention is to overcome the problem that the silicon-carbon negative electrode material in the prior art high-nickel ternary positive electrode and silicon-carbon negative electrode system battery is prone to failure during the cycle due to the dissolution of transition metal ions in the ternary material, and a lithium-ion secondary battery (hereinafter referred to as battery) is proposed. The present invention adjusts the content of element Si in the negative electrode active material by the blending amount of silicon-carbon material in the battery system, and matches the ternary material with a suitable molar content of element Ni accordingly, and proposes the relationship between the content of element Si in the negative electrode active material and the average sphericity of the silicon-carbon material and the molar content of element Ni in the ternary material, thereby solving the cycle failure problem of the battery.
[0004] In the prior art, silicon-carbon materials not only have the problem of cyclic expansion, but also the SEI film formed on its surface has a decreased stability due to the dissolution of transition metal ions in the ternary material. It also causes the SEI film to repeatedly break-regenerate-break during the charge-discharge cycle, causing the SEI film thickness to grow rapidly. This problem not only accelerates the consumption of electrolyte, but also affects the lithium ion (Li +) transmission efficiency, and at the same time, it will increase the difficulty of lithium ion embedding into silicon carbon, resulting in lithium plating on the silicon carbon surface. The lithium metal layer that can grow on the silicon carbon surface will further accelerate the failure of the battery, causing its cycle capacity to "dive" attenuate. At the same time, as the lithium dendrites grow, the diaphragm is punctured, eventually causing the battery to deform and short-circuit. In response to this problem, the inventors of the present invention have found through experiments that in the dissolution of transition metals in ternary materials, the element Ni is in a relatively high redox active state in the ternary material, and the redox potential of nickel is relatively suitable, so that the nickel element can effectively participate in the charge transfer reaction during the charge and discharge process, providing a stable electrode environment. This redox activity helps to form a more stable SEI film and reduce the instability caused by the decomposition of the electrolyte. The element Mn is highly soluble in the ternary material; the element Co may undergo redox reactions with the components in the electrolyte at high voltage to generate unstable substances such as peroxides, and these reactions will lead to the decomposition of the electrolyte. Therefore, the elements Mn and Co in the ternary material will both reduce the stability of the SEI film on the surface of the silicon carbon material. As the cycle progresses, the thickness of the SEI film increases significantly, resulting in the inability of lithium ions to embed into the silicon-carbon particles, causing the battery capacity to decay rapidly and eventually fail. Therefore, the inventors of the present invention propose that the molar content of the element Ni in the ternary material (the sum of the molar contents of the element Ni, the element Mn, and the element Co is 100%) can be adjusted according to the amount of silicon-carbon blended in the negative electrode active material, so as to effectively control the transition metal ions (Ni + , Mn 2+ ,Co 2+ ) content, thereby improving the stability of the SEI film generated on the surface of the silicon-carbon material, thereby avoiding rapid decay or failure of the cycle; further, the morphology and specific surface area of the silicon-carbon material can be regulated by adjusting and optimizing the average sphericity of the silicon-carbon material, thereby further improving the cycle performance and service life of the battery.
[0005] Based on this, the inventor of the present invention proposed the following technical solution:
[0006] A lithium ion secondary battery comprises a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode active material, the negative electrode sheet comprises a negative electrode active material, the positive electrode active material comprises a ternary material, and the negative electrode active material comprises a silicon-carbon material; the molar content of the element Ni in the ternary material is x, the average sphericity of the silicon-carbon material is S, the weight content of the element Si in the negative electrode active material is α, and x, S and α satisfy the formula x=k[0.06ln(α)+1+(1-S) / 30], 0.967≤k≤1.042, 0%<α≤30%, 0.55≤S≤0.9, x<0.95; the average particle size of the silicon-carbon material is β, 6μm≤β≤20μm, and k is a coefficient.
[0007] Compared with the prior art, the present invention has at least the following beneficial effects:
[0008] (1) In the present invention, the molar content of the element Ni in the ternary material is adjusted according to the content of the element Si in the negative electrode active material, which can effectively control the content of transition metal ions deposited on the negative electrode, thereby improving the stability of the SEI film generated on the surface of the silicon-carbon material, thereby avoiding lithium plating and the formation of lithium dendrites, and solving the problems of battery failure, battery deformation, and short circuit during the cycle.
[0009] (2) In the present invention, the size and specific surface area of the silicon-carbon material can be controlled by adjusting and optimizing the average sphericity of the silicon-carbon material. On the basis of adjusting the content of the element Si in the negative electrode active material, the molar content of the element Ni in the ternary material is further refined, thereby improving the cycle performance and service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 It is a schematic diagram of the relationship curve between α and x in the present invention.
[0011] Figure 2 This is a cross-sectional scanning electron microscope (SEM) image of a negative electrode sheet obtained by disassembling a fully charged battery after a battery cycle test of 300T in one embodiment of the present invention.
[0012] Figure 3 FIG. 1 is a Raman spectrum of a silicon-carbon material in one embodiment of the present invention.
[0013] Figure 4 FIG. 4 is a DQ / DV curve of a battery in one embodiment of the present invention.
[0014] Figure 5 This is a cross-sectional SEM image of the negative electrode sheet obtained by disassembling the battery after a full charge test of 300T in a comparison of the present invention. Specific implementation methods
[0016] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0017] The present invention provides a lithium ion secondary battery, which comprises a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode active material, the negative electrode sheet comprises a negative electrode active material, the positive electrode active material comprises a ternary material, and the negative electrode active material comprises a silicon-carbon material.
[0018] In the present invention, the molar content of the element Ni in the ternary material is x, the average sphericity of the silicon-carbon material is S, the weight content of the element Si in the negative electrode active material is α, and x, S and α satisfy the formula x=k[0.06ln(α)+1+(1-S) / 30], 0.967≤k≤1.042, 0%<α≤30%, 0.55≤S≤0.9, x<0.95; k is a coefficient, for example, k can be 0.96 7, 0.97, 0.98, 0.99, 1, 1.01, 1.02, 1.03, 1.04, 1.042, or a range consisting of any two thereof; for example, x can be 0.1, 0.3, 0.6, 0.62, 0.64, 0.66, 0.68, 0.7, 0.72, 0.74, 0.76, 0.78, 0.8, 0.84, 0.88, 0.9, 0.92, or a range consisting of any two thereof.
[0019] In one embodiment, 1.004≤k≤1.033.
[0020] In the structural design of the battery, the matching of the positive and negative electrodes is conducive to improving the performance of the battery. For batteries with a silicon-carbon negative electrode-ternary positive electrode system, when the negative electrode active material contains more silicon elements, the silicon elements will react with the electrolyte to generate some unstable compounds, which usually affect the stability of the SEI film and weaken the protective effect of the SEI film; while the element Ni in the ternary material is in a high redox active state, so that the nickel element can effectively participate in the charge transfer reaction during the charge and discharge process. This redox activity helps to form a more stable SEI film. The inventors of the present invention have found that the content x of the element Ni in the ternary material is related to the weight content α of the element Si in the negative electrode active material. The matching of x and α can stabilize the SEI film on the surface of the negative electrode material and improve the matching degree of the positive and negative electrodes, which is conducive to improving the cycle stability of the battery.
[0021] Furthermore, the stability of the SEI film can also be improved by regulating the average sphericity of the silicon-carbon material. This is because the negative electrode material undergoes volume expansion and contraction during the charge and discharge process. Particles with higher sphericity can evenly disperse stress, avoid stress concentration, and reduce cracks and ruptures caused by volume changes during the charge and discharge process. On a smoother surface, the SEI film can usually maintain continuity and integrity and is not easy to break.
[0022] It can be understood that the meaning of the formula x=k[0.06ln(α)+1+(1-S) / 30] is: the negative electrode active material includes silicon-carbon material. When the average sphericity of the silicon-carbon material and the weight content of the element Si in the negative electrode active material are determined, that is, when S and α are certain values, the corresponding 0.06ln(α)+1+(1-S) / 30 is also a specific value; in other words, when the average sphericity of the silicon-carbon material and the weight content of the element Si in the negative electrode active material are determined, a positive electrode material must be matched at this time, and the Ni element content x of the positive electrode material is less than 0.95. Therefore, according to the above formula, the negative electrode is matched with a ternary positive electrode material with a suitable nickel content, which improves the stability of the SEI film, thereby improving the cycle performance of the battery and avoiding the problem of cycle failure. It is worth noting that the aforementioned S, α and k need to be taken within their respective ranges, and the value is a fixed value.
[0023] On the other hand, the above formula can be regarded as consisting of two parts: "0.06ln(α)+1" and "(1-S) / 30", where "0.06ln(α)+1" reflects the relationship between the weight content α of the element Si in the negative electrode active material and the molar content x of the element Ni in the ternary material. That is, in the stage where the mass content of the element Si in the negative electrode active material is relatively small (for example, based on the total weight of the negative electrode active material, the content of the element Si in the negative electrode active material is 0%-6%), compared with the pure graphite negative electrode, the SEI film of the silicon-carbon material is more sensitive to the transition metals (Ni, Co, Mn) dissolved from the ternary material. Therefore, at this stage, as α increases, it is necessary to quickly increase the molar content of the Ni element in the ternary material to stabilize the SEI film, and simultaneously reduce the molar content of the Co element and the Mn element, thereby reducing the damage to the stability of the SEI film and avoiding failure of the silicon-carbon material; and in the negative electrode active material, the mass content of the element Si is relatively large (for example For example, when the content of element Si in the negative electrode active material in the electrode is 6%-30% based on the total mass of the negative electrode active material), when the molar content of the Ni element in the positive electrode is increased to a certain value, the content of the Co element and the Mn element is also reduced to a certain value at the same time. At this time, the SEI film generated on the silicon-carbon surface has good stability, and the small amount of Co and Mn elements dissolved from the positive electrode can be approximately considered to be uniformly distributed on the negative electrode sheet. The amount of transition metal elements deposited on the surface of each silicon-carbon particle is basically the same, and does not change significantly with the increase of the silicon content in the electrode sheet. Therefore, at this stage, the molar content of the Ni element in the ternary material no longer needs to increase rapidly. However, as the molar content of the Ni element in the ternary material increases, its structural stability will also deteriorate, and the battery is prone to gas production in a high temperature environment. For comprehensive consideration of performance, the molar content of the Ni element in the ternary material should be controlled within the upper and lower limits of the calculated value of the formula. The relationship curve between α and x in the present invention is as follows Figure 1 shown.
[0024] In the formula, "(1-S) / 30" reflects the relationship between the average sphericity of the silicon-carbon material and the molar content x of the element Ni in the ternary material. When the average sphericity of the silicon-carbon material is in the range of 0.55≤S≤0.9, it is beneficial to improve the stability of the negative electrode. When the average sphericity of the silicon-carbon material is near 0.55, the morphology of silicon carbon is irregular. At this time, silicon carbon has a larger specific surface area, which means that the area of contact between its surface and the electrolyte is increased. During the charge and discharge process, the reaction between the surface of the silicon-carbon material and the electrolyte is more intense, and a thicker SEI film is usually formed. At this time, in order to stabilize the SEI film of the negative electrode, it is necessary to increase the Ni element in the ternary material; when the average sphericity of the silicon-carbon material is near 0.9, the silicon-carbon material is close to a sphere. At this time, the specific surface area of the silicon-carbon material is small, and fewer side reactions occur on the surface of the negative electrode material, so less Ni is required.
[0025] In summary, the inventors of the present invention have found through experimental analysis that the stability of the SEI film generated on the surface of the silicon-carbon material is closely related to the content of transition metal ions deposited on the negative electrode. Compared with "(1-S) / 30", "0.06ln(α)+1" plays a major role in improving the stability of the negative electrode SEI film, that is, the relationship between the weight content α of the element Si in the negative electrode active material and the molar content x of the element Ni in the ternary material plays a major role in stabilizing the negative electrode SEI film.
[0026] In the present invention, as the content of element Si in the negative electrode active material increases, more SEI film is generated on the surface of the silicon-carbon material, so more Ni elements are needed to improve the stability of the SEI film. At the same time, the deposition of elements Co and Mn on the SEI film should also be reduced to avoid the SEI film from breaking and regenerating during the cycle, which increases the thickness of the SEI film and makes it difficult for lithium ions to be embedded, eventually leading to battery failure. When the molar content of element Si in the negative electrode active material is adjusted to match the molar content of element Ni in the ternary material, a control range is required: when the molar content of Ni in the positive electrode is too low and the molar content of Co and Mn is too high, the transition metal elements deposited on the negative electrode are insufficient in Ni and excessive in Co and Mn, resulting in poor stability of the SEI film formed on the surface of the silicon-carbon material. After a period of circulation, serious black spots and lithium precipitation appear on the surface of the negative electrode, which leads to a sudden decrease in battery capacity. When the molar content of element Ni is too high, the high-nickel positive electrode is more likely to undergo an irreversible phase transition from H2 phase to H3 phase during the electrochemical cycle, the volume anisotropy changes to a large extent, and the stability of the ternary material structure decreases, which also causes the battery capacity to decay rapidly during the cycle. At the same time, the battery is more likely to bulge and deform in a high temperature environment.
[0027] like Figure 2The figure shows a cross-sectional SEM image of the negative electrode sheet obtained by disassembling a fully charged battery after a battery cycle test of 300T in one embodiment of the present invention. It can be seen from the figure that when the molar content of the element Ni in the ternary material is optimized, the thickness of the SEI film on the surface of the silicon-carbon material is relatively small, about 1.4μm, and the structure of the SEI film is relatively complete without significant deformation.
[0028] In the present invention, x, S and α only perform numerical calculations when performing the formula x=k[0.06ln(α)+1+(1-S) / 30], and the unit does not participate in the calculation. For example, when k=1.02, α=15%, and S=0.8, x=k[0.06ln(α)+1+(1-S) / 30]=1.02×[0.06×ln(0.15)+(1-0.8) / 30]=0.911.
[0029] In the present invention, the contents of the elements Ni, Co, Mn in the ternary material and the element Si in the silicon-carbon material can be obtained by conventional testing methods in the art, such as inductively coupled plasma atomic emission spectroscopy (ICP-AES) and X-ray fluorescence spectroscopy (XRF).
[0030] In the present invention, the average particle size of the silicon-carbon material is β, 6μm≤β≤20μm, for example, 6μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm or 20μm.
[0031] In one embodiment, 7.5 μm≤β≤11 μm.
[0032] In the present invention, when β>20μm, the average particle size of the silicon-carbon material is too large, which will make the silicon-carbon material more easily broken during the rolling process, increase the cyclic expansion of the negative electrode sheet, and affect the battery cycle performance; when β<6μm, the specific surface area of the silicon-carbon material is large, which will intensify the side reactions on the surface of the negative electrode sheet and increase the risk of battery inflation.
[0033] In the present invention, the average particle size of the silicon-carbon material can be obtained by conventional testing methods in the art, such as first obtaining a high-resolution image through a scanning electron microscope, and then performing particle size measurement and distribution statistics through electron microscope image analysis software such as ImageJ to obtain the average particle size. The model of the scanning electron microscope is HITACHISU5000 / SU8600.
[0034] In the present invention, the ternary material includes a single crystal material and a polycrystalline material, and the mass fraction of the single crystal material in the positive electrode active material is r, 70%≤r≤90%, for example, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89% or 90%.
[0035] In one embodiment, 75%≤r≤85%.
[0036] In the present invention, the ternary material includes a single crystal material and a polycrystalline material, the single crystal material has good cycle stability and thermal stability, and the polycrystalline material has good rate performance. The two are mixed in a suitable ratio to improve the compaction density, gram capacity and rate performance of the positive electrode, and also keep the positive electrode in good thermal stability. When r < 70%, it indicates that the proportion of polycrystalline material in the ternary material is too high, the cycle performance and thermal stability of the positive electrode are poor, and the battery will experience rapid capacity decay and premature gas production in a high temperature environment; and when r > 90%, it indicates that the proportion of polycrystalline material in the ternary material is too low, the gram capacity and compaction of the positive electrode are low, resulting in a decrease in the energy density of the battery, and at the same time, the fast charging performance of the positive electrode is poor. Under high rate charge and discharge, the dynamics of the battery are insufficient, resulting in accelerated positive electrode aging and premature failure of the battery.
[0037] In the present invention, the single crystal material and the polycrystalline material in the ternary material can be measured by conventional testing methods in the field, such as using an ion beam to cut the positive electrode sheet along the thickness direction to obtain a cross section, then imaging the cross section through a scanning electron microscope, and performing image analysis on the obtained cross section: for single crystal materials, their cross-sectional images usually show clear grain boundaries and crystal structures, while polycrystalline materials may show multiple grains with different orientations.
[0038] In the present invention, the mass fraction of single crystal material and polycrystalline material in the positive electrode active material can be obtained by conventional testing methods in the field, for example, by the following method: first disassemble the battery to obtain the positive electrode sheet, use an argon ion polisher ArFar100 to treat it, obtain a cross-sectional sample of the positive electrode sheet, obtain a high-resolution image through a scanning electron microscope, and then use electron microscope image analysis software such as ImageJ to calculate the cross-sectional area (P1) of the single crystal ternary and the cross-sectional area (P2) of the polycrystalline ternary. The mass fraction of the single crystal material in the positive electrode active material can be obtained by calculation using the formula r=P1 / (P1+P2), and then the mass fraction of the polycrystalline material in the positive electrode active material can be indirectly calculated.
[0039] In the present invention, the average particle size of the ternary material is 2μm-8μm, for example, 2μm, 2.2μm, 2.4μm, 2.6μm, 2.8μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm or 8μm.
[0040] In one embodiment, the average particle size of the ternary material is 4 μm-6 μm.
[0041] In the present invention, the average particle size of the single crystal material is 1μm-5μm, for example, 1μm, 2μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3μm, 3.2μm, 3.4μm, 3.6μm, 3.8μm, 4μm, 4.2μm, 4.4μm, 4.6μm, 4.8μm or 5μm.
[0042] In one embodiment, the average grain size of the single crystal material is 3 μm-4 μm.
[0043] In the present invention, the average grain size of the polycrystalline material is 8 μm-15 μm, for example, 8 μm, 8.2 μm, 8.4 μm, 8.6 μm, 8.8 μm, 9 μm, 9.2 μm, 9.4 μm, 9.6 μm, 9.8 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm or 15 μm.
[0044] In one embodiment, the average grain size of the polycrystalline material is 10 μm-13 μm.
[0045] In the present invention, the average particle size of the ternary material can be further regulated by adjusting the average particle size of the polycrystalline material and the single crystal material. Similarly, regulating the average particle size of the ternary material also has the effect of regulating the content of the single crystal material and the polycrystalline material. A reasonable average particle size range of the ternary material helps to improve the cycle performance of the battery and avoid cycle failure. When the average particle size of the ternary material is less than 2 μm, the positive electrode active material is mainly composed of single crystal materials with a smaller average particle size. If the average particle size of the ternary material is too small, the gram capacity will be significantly reduced. At the same time, due to the poor rate performance, the positive electrode will accelerate aging under high rate charge and discharge; when the average particle size of the ternary material is greater than 8 μm, the positive electrode active material is mainly composed of polycrystalline materials with a larger average particle size. The specific surface area of the polycrystalline material is too large, and the side reaction with the electrolyte is aggravated, resulting in the battery bulging during the cycle test.
[0046] In the present invention, the average particle size of the single crystal material, the average particle size of the polycrystalline material and the average particle size of the ternary material can all be determined by conventional testing methods in the art, such as obtaining a high-resolution image by a scanning electron microscope, and then performing particle size measurement and distribution statistics by electron microscope image analysis software such as ImageJ to obtain the average particle size. The model of the scanning electron microscope is HITACHISU5000 / SU8600.
[0047] In the present invention, the molar content of element Si in the silicon-carbon material is For example, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 42%, 44%, 46%, 48%, 50%, 55%, 60%, 65% or 70%.
[0048] In one embodiment,
[0049] In the present invention, the molar content of the element Si in the silicon-carbon material is related to the energy density and cycle expansion of the battery. Regulating its content helps to improve the energy density while reducing the cycle expansion problem. When , the gram capacity of silicon-carbon material is low, which is not conducive to the improvement of battery energy density; when When the temperature is high, the silicon-carbon material has poor stability and large expansion, which increases the risk of battery deformation.
[0050] In the present invention, the molar content of the element Si in the silicon-carbon material can be measured by conventional testing methods in the art, for example, by disassembling the battery to obtain the negative electrode sheet, treating the electrode sheet cross section with an argon ion polisher, performing SEM imaging on the cross section to obtain a visible cross-sectional SEM image of the silicon-carbon material, and measuring the Si / C ratio in the middle of the cross section of the silicon-carbon material by EDS point scanning.
[0051] In the present invention, the weight content of element Si in the negative electrode active material is α, 0%<α≤30%, for example, 0.1%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 14%, 16%, 18%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or 30%.
[0052] In one embodiment, 7.5%≤α≤21%.
[0053] In the present invention, the weight content α of the element Si in the negative electrode active material can be determined by conventional testing methods in the art, for example, by the following method: disassembling the battery, taking out the negative electrode sheet, soaking and cleaning it with dimethyl carbonate (DMC) and then drying it, removing the copper foil, and obtaining the negative electrode coating powder, placing the negative electrode coating powder in an argon atmosphere, heating it to 250°C at 10°C / min, and taking the weight of the negative electrode coating powder at this time as the initial weight W1, and then switching to an air atmosphere, heating it to 900°C at 10°C / min and maintaining it for 8h, and obtaining the final weight W2 of the negative electrode coating powder. The content α of the Si element in the negative electrode active material can be calculated by the formula α=6W2 / 15W1.
[0054] In the present invention, the specific surface area of the silicon-carbon material is γ, 1m 2 / g≤γ≤1.4m 2 / g, for example, 1m 2 / g, 1.02m 2 / g, 1.24m 2 / g, 1.06m 2 / g, 1.08m 2 / g, 1.1m 2 / g, 1.12m 2 / g, 1.14m 2 / g, 1.16m 2 / g, 1.18m 2 / g, 1.2m 2 / g, 1.22m 2 / g, 1.24m 2 / g, 1.26m 2 / g, 1.28m 2 / g, 1.3m 2 / g or 1.4m 2 / g.
[0055] In one embodiment, 1.1 m 2 / g≤γ≤1.3m 2 / g.
[0056] In the present invention, regulating the specific surface area of the silicon-carbon material within a certain range is beneficial to improving the capacity and cycle life of the battery. When the specific surface area of the silicon-carbon material is too large, more lithium ions will be consumed, resulting in a decrease in the first coulombic efficiency of the battery; and when the specific surface area of the silicon-carbon material is too small, the diffusion of lithium ions between the negative electrode active materials will be restricted, resulting in a decrease in the battery capacity and cycle life.
[0057] In the present invention, the specific surface area of the silicon-carbon material can be measured by conventional testing methods in the art, such as using the Brunauer-Emmett-Teller (BET) test method, such as using a TriStarⅡ specific surface area analyzer for measurement, with N2 as the adsorbed gas.
[0058] In the present invention, the average sphericity of the silicon-carbon material is S, 0.55≤S≤0.9, for example, 0.55, 0.56, 0.58, 0.6, 0.62, 0.64, 0.66, 0.68, 0.7, 0.72, 0.74, 0.76, 0.78, 0.8, 0.82, 0.84, 0.86, 0.88 or 0.9.
[0059] In one embodiment, 0.6≤S≤0.85.
[0060] In the present invention, the morphology of the silicon-carbon material can be regulated by regulating its average sphericity. When S is less than 0.55, it indicates that the morphology of the silicon-carbon material is irregular. During rolling, the silicon-carbon particle material is prone to varying degrees of breakage due to uneven force, which not only leads to a decrease in the initial efficiency of the battery, but also aggravates the cyclic expansion of the negative electrode sheet; when S is greater than 0.9, it indicates that the morphology of the silicon-carbon material is close to a sphere. Although the compressive resistance of the silicon-carbon material is greatly improved, its bonding performance will deteriorate. Since the volume of the silicon-carbon material changes significantly during the charge and discharge process, due to insufficient bonding force, the silicon-carbon materials will also have poor contact in the later stage of the cycle, which in turn affects the embedding and extraction of lithium ions, resulting in black spots and lithium precipitation on the negative electrode sheet.
[0061] In the present invention, the average sphericity can be analyzed by image processing software (such as ImageProPlus) on the image of each particle in the SEM photograph of the negative electrode coating at a certain magnification (such as 2500 times), and the circumference and area of each particle are obtained, and the circumference equivalent radius r1 and the area equivalent radius r2 of each particle are calculated respectively. The sphericity of each particle S=r2 / r1, and then the sphericity of each particle is quantitatively weighted averaged to obtain the average sphericity of the silicon-carbon material.
[0062] In the present invention, the negative electrode active material also includes a carbon-based material, and the average particle size of the carbon-based material is 5μm-15μm, for example, 5μm, 5.2μm, 5.4μm, 5.6μm, 5.8μm, 6μm, 6.2μm, 6.4μm, 6.6μm, 6.8μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm or 15μm.
[0063] In one embodiment, the average particle size of the carbon-based material is 8 μm-12 μm.
[0064] In the present invention, the carbon-based material includes at least one of artificial graphite, natural graphite, mesophase carbon microbeads, soft carbon and hard carbon.
[0065] In the present invention, the average particle size of the carbon-based material has a certain influence on the kinetic performance. When the average particle size of the carbon-based material is too large (>15μm), the embedding path of lithium ions in the carbon-based material will be too large, resulting in poor kinetics of the carbon-based material. When charging at a higher rate, lithium deposition is prone to occur in the negative electrode sheet; when the particle size of the carbon-based material is too small (<5μm), the gram capacity and compaction density of the carbon-based material are reduced, resulting in too low energy density of the battery.
[0066] In the present invention, the average particle size of the carbon-based material can be determined by conventional testing methods in the art, for example, by obtaining a high-resolution image through a scanning electron microscope, and then performing particle size measurement and distribution statistics through electron microscope image analysis software such as ImageJ to obtain the average particle size. The model of the scanning electron microscope is HITACHISU5000 / SU8600.
[0067] In the present invention, the ternary material includes a chemical formula of LiNi x Co y Mn z M a The substance of O2, M includes at least one of element Al, element Zr, element Mg, element Y, element Ti, element B, element Sr, element W, element Si, element La and element Nb.
[0068] In the present invention, 0.65≤x<0.95, for example, 0.65, 0.66, 0.67, 0.68, 0.69, 0.7, 0.72, 0.74, 0.76, 0.78, 0.8, 0.82, 0.84, 0.86, 0.88, 0.9, 0.92 or 0.94; 0≤y≤0.35, for example, 0.01, 0.03, 0.06, 0.09, 0.12, 0.14, 0.16, 0.18, 0.2, 0.25, 0.3, 0.31, 0 0≤z≤0.35, for example, 0.01, 0.03, 0.06, 0.09, 0.12, 0.14, 0.16, 0.18, 0.2, 0.25, 0.3, 0.31, 0.32, 0.33 or 0.34; 0≤a≤0.05, for example, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.042, 0.044, 0.046, 0.048 or 0.049.
[0069] In one embodiment, 0.9≤x<0.95, 0.02≤y≤0.06, 0.01≤z≤0.03.
[0070] In one embodiment, the ternary material comprises at least a combination of element Al, element Mg and element Ti, and the sum of the molar contents of the element Al, the element Mg and the element Ti is 800ppm-8000ppm, for example, 800ppm, 810ppm, 815ppm, 820ppm, 825ppm, 830ppm, 840ppm, 850ppm, 860ppm, 880ppm, 900ppm, 950ppm, 1000ppm, 1 500ppm, 2000ppm, 2500ppm, 3000ppm, 4000ppm, 5000ppm, 6000ppm, 6500ppm, 7000ppm, 7200ppm, 7400ppm, 7600ppm, 7800ppm, 7850ppm, 7900ppm, 7920ppm, 7940ppm, 7960ppm, 7980ppm, 7985ppm, 7990ppm or 8000ppm.
[0071] In one embodiment, the sum of the molar contents of the element Al, the element Mg and the element Ti is 2000ppm-5000ppm.
[0072] In one embodiment, the molar content ratio of the element Al, the element Mg and the element Ti is 2:1:1.
[0073] In the present invention, the elements Al, Zr, Mg, Y, Ti, B, Sr, W, Si, La and Nb are used in ternary materials to improve the conductivity, structural stability and thermal stability of the ternary materials, thereby improving the cycle stability and safety of the battery. When the sum of the contents of the elements Al, Mg and Ti in the ternary materials is less than 800ppm, the degree of cation mixing of the ternary materials is high, resulting in poor electrochemical performance and thermal stability of the battery; and when the sum of the contents of the elements Al, Mg and Ti is greater than 8000ppm, it is easy to cause lattice distortion, weakened interlayer bonding strength and reduced conductivity in the ternary materials, resulting in decreased cycle performance of the battery.
[0074] In the present invention, the values of x, y, and z can be determined by conventional testing methods in the art, for example, by the following method: take about 0.1 g of the ternary material as a sample, add 10 mL of hydrochloric acid and digest it on a 350° C. hot plate for 10 min. After cooling, fix the volume to 100 mL, dilute it 10 times, take part of the solution and analyze it with an ICP spectrometer, and after obtaining the corresponding test parameters, x, y, and z can be obtained by converting them through the formula.
[0075] In the present invention, the element Al, element Zr, element Mg, element Y, element Ti, element B, element Sr, element W, element Si, element La and element Nb can be measured by conventional testing methods in the art, for example, by testing with an ICP spectrometer, and the testing method is as follows: take 0.1 g of the ternary material as a sample, add 10 mL of hydrochloric acid and digest it on a 350° C. hot plate for 10 min, cool it, set the volume to 100 mL, dilute it 10 times, take part of the solution and analyze it with an ICP spectrometer, and the corresponding test parameters of the doping elements can be obtained.
[0076] In the present invention, the negative electrode sheet further comprises a negative electrode current collector and a negative electrode coating on at least one side of the surface of the negative electrode current collector.
[0077] In the present invention, the porosity of the negative electrode coating is C, 20%≤C≤50%, for example, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48% or 50%.
[0078] In one embodiment, 30%≤C≤40%.
[0079] In the present invention, regulating the porosity of the negative electrode coating is conducive to good contact between the negative electrode active material and the electrolyte, and improving the electron transmission performance. When the porosity is less than 20%, the space inside the negative electrode coating that can accommodate the electrolyte is insufficient, which is not conducive to the ion transmission between the negative electrode active materials, and also increases the overvoltage risk of the negative electrode sheet, resulting in the breakage of the silicon-carbon material; when the porosity is greater than 50%, the contact between the silicon-carbon materials is not tight enough, which is not conducive to the transmission of electrons, and the residual amount of the electrolyte inside the negative electrode coating is too high, which aggravates the side reaction between the silicon-carbon material and the electrolyte, resulting in bulging of the battery in the high-temperature performance test.
[0080] In the present invention, the porosity of the negative electrode coating can be determined by conventional testing methods in the art, such as testing by a gas replacement method, and the specific method is as follows: after the lithium-ion secondary battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and then soaked in a DMC solvent for 12 hours and then rinsed with DMC to remove the lithium salt attached to the electrode sheet. After drying, the negative electrode sheet is cut into discs with a diameter of 12 mm using a slicer, and the thickness of 20 discs is measured with a micrometer, and the volume of each disc is calculated and summed to obtain the sum of the volumes of the 20 discs V1; then a true density meter (such as the JW-M100A fully automatic true density tester of Jingwei Gaobo) is used to test the true volume V2 of the 20 discs, wherein the test gas is helium and the test environment temperature is 25±2°C; then the porosity C of the negative electrode sheet is (V1-V2) / V1×100%.
[0081] In the present invention, the OI value of the negative electrode coating is δ, 10%≤δ≤22%, for example, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21% or 22%.
[0082] In one embodiment, 14%≤δ≤18%.
[0083] In the present invention, adjusting the OI value of the negative electrode coating plays an important role in optimizing the insertion and extraction rates of lithium ions. When the OI value δ of the negative electrode coating is less than 10%, the initial expansion of the negative electrode coating along the thickness direction is too small, and the space inside the negative electrode coating that can accommodate the electrolyte is small; and when the OI value δ of the negative electrode coating is greater than 22%, the cyclic expansion of the negative electrode coating along the thickness direction is too large, and the contact between the particles is not close enough. Both of these situations will lead to poor dynamics of the negative electrode sheet.
[0084] In the present invention, the OI value of the negative electrode coating can be determined by conventional testing methods in the art, for example, by an X-ray powder diffractometer. The specific method is as follows: after the lithium-ion secondary battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and then soaked in a dimethyl carbonate (DMC) solvent for 12 hours, and then rinsed with DMC to remove the lithium salt attached to the negative electrode sheet. After drying, it is tested with an X-ray powder diffraction instrument (such as Shimadzu XRD-6100 X-ray diffractometer). The diffraction peak appearing at 2θ=54-55° in the obtained diffraction spectrum is the (004) peak of the carbon-based material, and the intensity is recorded as I004. The diffraction peak appearing at 2θ=77-78° is the (110) peak of the carbon-based material, and the intensity is recorded as I110. The OI value of the negative electrode coating δ=I004 / I110.
[0085] In the present invention, the positive electrode sheet further comprises a positive electrode current collector and a positive electrode coating on at least one side of the positive electrode current collector, and the negative electrode sheet further comprises a negative electrode current collector and a negative electrode coating on at least one side of the negative electrode current collector.
[0086] In the present invention, the capacity per unit area of the positive electrode coating is E, the capacity per unit area of the negative electrode coating is D, 1.02≤D / E≤1.13, for example, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.1, 1.11, 1.12 or 1.13.
[0087] In one embodiment, 1.05≤D / E≤1.1.
[0088] In the present invention, the ratio D / E between the capacity E per unit area of the positive electrode coating and the capacity D per unit area of the negative electrode coating can reflect whether the positive and negative electrode capacities match, and regulating the value of D / E can optimize the cycle performance and safety of the battery during the charge and discharge process. When D / E < 1.02, the capacity of the negative electrode sheet is too low relative to the positive electrode sheet, and the negative electrode sheet has the risk of lithium deposition; when D / E > 1.13, the capacity of the positive electrode sheet is too low relative to the negative electrode sheet, which is not conducive to improving the energy density of the battery.
[0089] In the present invention, the capacity E per unit area of the positive electrode coating and the capacity D per unit area of the negative electrode coating can be obtained by conventional testing methods in the art, for example:
[0090] (1) The test method for the capacity D per unit area of the negative electrode coating is as follows: the negative electrode sheet is lithium-intercalated at a current of 0.05C. When the potential reaches 5mV (relative Li / Li + ), let it stand for 10 minutes, insert lithium into the negative electrode again with a current of 0.02C, and when the potential reaches 5mV, let it stand for 10 minutes, and then remove lithium from the negative electrode with a current of 0.05C until the potential reaches 0.9V (relative Li / Li + ); the above procedure was cycled 3 times, and the capacity D per unit area of the negative electrode coating was obtained by dividing the third lithium de-ion capacity by the surface area of the negative electrode sheet.
[0091] (2) The test method for the capacity E per unit area of the positive electrode coating is as follows: the positive electrode sheet is delithiated at a current of 0.05C. When the potential reaches 4.35V (relative Li / Li + ), let it stand for 10 minutes, and then remove lithium from the positive electrode again with a current of 0.02C. When the potential reaches 4.35V, let it stand for 10 minutes, and then insert lithium into the positive electrode with a current of 0.05C until the potential reaches 3.3V (relative Li / Li + ); the above procedure was cycled 3 times, and the capacity E per unit area of the positive electrode coating was obtained by dividing the third lithium insertion capacity by the surface area of the positive electrode sheet.
[0092] In the present invention, in the Raman spectrum of the silicon-carbon material, at 470 cm -1 -480cm-1 The first characteristic peak is at 507cm -1 -517cm -1 There is a second characteristic peak at 1330cm -1 -1350cm -1 It has a third characteristic peak at 1590cm -1 -1610cm -1 It has a fourth characteristic peak; the intensity L1 of the first characteristic peak, the intensity L2 of the second characteristic peak, the intensity L3 of the third characteristic peak and the intensity L4 of the fourth characteristic peak satisfy 0.5≤(L1+L3) / (L2+L4)≤3, for example, 0.5, 1, 1.5, 2, 2.5 or 3.
[0093] In one embodiment, the silicon-carbon material is prepared by a chemical vapor deposition process.
[0094] In one embodiment, the silicon-carbon material includes a porous carbon substrate, silicon dispersed in pores of the porous carbon substrate, and a carbon coating layer located on the surface of the porous carbon substrate.
[0095] In the present invention, in the Raman spectrum of the silicon-carbon material, (L1+L3) / (L2+L4) can reflect the crystallinity of the silicon-carbon material and the defects on the surface of the silicon-carbon material. When (L1+L3) / (L2+L4) is less than 0.5, the crystallinity of silicon in the silicon-carbon material is high, which will lead to large cycle expansion of the battery and poor cycle capacity retention rate. When (L1+L3) / (L2+L4) is greater than >3, the silicon-carbon material has too many surface defects, resulting in its first coulombic efficiency being too low, which is not conducive to improving the battery energy density.
[0096] like Figure 3 The Raman spectrum of the silicon-carbon material in one embodiment of the present invention is shown. As shown in the figure, there are four characteristic peaks at different positions. The first characteristic peak represents amorphous carbon, the second characteristic peak represents crystalline silicon, the third characteristic peak represents the defect degree of the material, and the fourth characteristic peak represents the order degree of the material.
[0097] In the present invention, the Raman spectrum of the silicon-carbon material is obtained by conventional testing methods in the art, for example, using a ThermoFisher Raman spectrometer with a test wave number range of 400 cm -1 -4000cm -1 .
[0098] In the present invention, the ratio of the intensity of the characteristic peak 2 at 4.1V-4.2V to the intensity of the characteristic peak 1 at 3.9V-4.1V of the DQ / DV curve of the lithium ion secondary battery in the 10th cycle of charging is G, 1.5≤G≤1.8, for example, 1.5, 1.52, 1.54, 1.56, 1.58, 1.6, 1.62, 1.64, 1.66, 1.68, 1.7, 1.75 or 1.8.
[0099] In the present invention, the characteristic peak in the DQ / DV curve of the lithium-ion secondary battery at the 10th cycle of charging can reflect the phase change and chemical reaction of the electrode during the charging and discharging process of the battery, and then infer the type of electrode material; Figure 4 The ratio G of the intensity of the characteristic peak 2 to the intensity of the characteristic peak 1, when G is less than 1.5, indicates that the molar content of the element Ni in the ternary material is too low, resulting in its low gram capacity, which is not conducive to the improvement of the battery energy density; when G is greater than 1.8, it indicates that the molar content of the element Ni in the ternary material is too high, resulting in its poor structural stability and poor battery cycle capacity retention rate.
[0100] In the present invention, the DQ / DV curve can be obtained by electrochemical testing, specifically as follows: under an environment of 25°C, the full battery is cycled, the charging rate is 2C, the discharging rate is 4C, the voltage range is 4.3-2.5V, the number of cycles is 10, and the data points of the charge and discharge curve are taken at an interval of 5S. The DQ / DV curve is made through the CV curve of the 10th cycle, and the ratio G of the intensity of characteristic peak 2 to the intensity of characteristic peak 1 is calculated.
[0101] In the present invention, the lithium-ion secondary battery further comprises an electrolyte, and the electrolyte comprises at least one of acetate, lithium salt and additives.
[0102] In one embodiment, the electrolyte includes the acetate, the lithium salt and the additive.
[0103] In one embodiment, the acetate includes 2,2-difluoroethyl acetate.
[0104] In the present invention, the mass content of the 2,2-difluoroethyl acetate in the electrolyte is η, 0.01≤η≤0.33, for example, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.08, 0.1, 0.12,
[0105] 0.14, 0.16, 0.18, 0.2, 0.24, 0.28, 0.3, 0.31, 0.32 or 0.33.
[0106] In one embodiment, 0.05≤η≤0.15.
[0107] In the present invention, an appropriate amount of 2,2-difluoroethyl acetate can help form a stable SEI film on the surface of the silicon-carbon material, help protect the surface of the negative electrode sheet, inhibit the continuous occurrence of side reactions, reduce the volume expansion of the negative electrode sheet during the charge and discharge process, and improve the battery cycle stability. When η<0.01, it indicates that the mass content of 2,2-difluoroethyl acetate in the electrolyte is too low, the interface film generated on the surface of the silicon-carbon material has low density and poor stability, and the negative electrode sheet is prone to black spot lithium precipitation in the cycle test, accelerating the cycle failure of the battery; when η>0.33, it indicates that the mass content of 2,2-difluoroethyl acetate in the electrolyte is too high, and the battery is prone to bulging in the performance test under high temperature environment.
[0108] In the present invention, the mass content of 2,2-difluoroethyl acetate in the electrolyte can be measured by conventional testing methods in the art, such as by gas chromatography or gas chromatography-mass spectrometry.
[0109] In the present invention, the lithium salt can be selected from the electrolyte lithium salts conventionally used in the art, including lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethylsulfonyl imide) (LiTFSI), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiDFOB), lithium bis(oxalatoborate) (LiBOB), lithium bis(fluorosulfonyl imide) (LiFSI) and lithium 4,5-dicyano-2-trifluoromethylimidazole (LiDTI), lithium difluorophosphate (LiPO2F2) and at least one of lithium difluorobis(oxalatophosphate).
[0110] In the present invention, the additive includes at least one of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), 1,3-propane sultone (PS), fluoroethylene carbonate (FEC), tetravinylsilane (TVS), tris(trimethylsilyl)borate (TMSB), hexamethyldisilazane (HMDS), fluorobenzene (FB), triphenyl phosphite (TPPi), benzonitrile, p-toluonitrile, 3,5-difluorobenzonitrile, adiponitrile (AND), succinonitrile (SN), glutaronitrile, suberonitrile, ethylene glycol bis(propionitrile) ether, 1,3,6-hexanetrinitrile (HTCN), 1,2,6-hexanetrinitrile and 1,2,3-tris(2-cyanoethoxy)propane.
[0111] In the present invention, the volume median particle size of the silicon-carbon material is 6 μm-20 μm, for example, 6 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm or 20 μm.
[0112] In one embodiment, the volume median particle size of the silicon-carbon material is 7.5 μm-11 μm.
[0113] In the present invention, the volume median particle size of the ternary material is 2μm-8μm, for example, 2μm, 2.2μm, 2.4μm, 2.6μm, 2.8μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, or 8μm.
[0114] In one embodiment, the volume median particle size of the ternary material is 4 μm-8 μm.
[0115] In the present invention, the volume median particle size of the single crystal material is 1μm-5μm, for example, 1μm, 2μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3μm, 3.2μm, 3.4μm, 3.6μm, 3.8μm, 4μm, 4.2μm, 4.4μm, 4.6μm, 4.8μm or 5μm.
[0116] In one embodiment, the volume median particle size of the single crystal material is 3 μm-4 μm.
[0117] In the present invention, the volume median particle size of the polycrystalline material is 8μm-15μm, for example, 8μm, 8.2μm, 8.4μm, 8.6μm, 8.8μm, 9μm, 9.2μm, 9.4μm, 9.6μm, 9.8μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm or 15μm.
[0118] In one embodiment, the volume median grain size of the polycrystalline material is 10 μm-13 μm.
[0119] In the present invention, the volume median particle size of the carbon-based material is 5μm-15μm, for example, 5μm, 5.2μm, 5.4μm, 5.6μm, 5.8μm, 6μm, 6.2μm, 6.4μm, 6.6μm, 6.8μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm or 15μm.
[0120] In one embodiment, the volume median particle size of the carbon-based material is 8 μm-12 μm.
[0121] In the present invention, the determination of the volume median particle size can be obtained by conventional testing methods in the art, such as by a laser particle size tester. Taking the ternary material as an example: after the lithium-ion secondary battery is discharged to 0% SOC, the positive electrode sheet is disassembled and taken out, and then soaked in a DMC solvent for 12 hours, and then rinsed with DMC to remove the lithium salt attached to the electrode sheet, the aluminum foil is removed, and the active material is baked at 100°C for 30 minutes to obtain the positive electrode coating powder; the Malvern particle size tester is used for measurement, and the test steps are as follows: the positive electrode coating powder is dispersed in deionized water containing a dispersant (such as nonylphenol polyoxyethylene ether, with a content of 0.02wt%-0.03wt%) to form a mixture, the mixture is ultrasonicated for 2 minutes, and then placed in a Malvern particle size tester for testing, and the corresponding particle size distribution data is obtained, thereby obtaining the volume median particle size value of the ternary material.
[0122] In the present invention, the positive electrode sheet also includes at least one of a positive electrode conductor, a positive electrode binder and a positive electrode dispersant, and the negative electrode sheet also includes at least one of a negative electrode conductor, a negative electrode binder and a negative electrode dispersant. The positive electrode conductor, positive electrode binder, positive electrode dispersant, negative electrode conductor, negative electrode binder and negative electrode dispersant are all conventional choices in the art.
[0123] In the present invention, the positive electrode current collector and the negative electrode current collector are both conventionally selected in the art.
[0124] In the present invention, the lithium-ion secondary battery further comprises a separator, and the separator can be a conventional one in the art.
[0125] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.
[0126] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0127] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.
[0128] Embodiment 1:
[0129] Preparation of negative electrode:
[0130] 70% artificial graphite (average particle size 9.81 μm) and 30% silicon carbon (average particle size β 9.4 μm, specific surface area γ 1.145 m 2 / g, average sphericity S is 0.683) for mechanical mixing for 5 minutes, and after mixing evenly, it is used as the negative electrode active material, wherein the molar content of element Si in silicon carbon is The weight content of element Si in the negative electrode active material is α=14.35%; the negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, SuperP, and single-walled carbon nanotubes are mixed in a mass ratio of 95:2:2:0.75:0.25, and an appropriate amount of water is added as a solvent. After being stirred evenly by a vacuum mixer, a negative electrode active slurry is obtained, and the negative electrode active slurry is evenly coated on the surface of a high-strength carbon-coated copper foil with a thickness of 6 μm to obtain a negative electrode coating; the coated negative electrode sheet is transferred to a vacuum drying oven and baked at 85° C. for 12 hours. After the negative electrode sheet is rolled by a double-roll roller press, a negative electrode sheet with a length of 66 mm and a width of 47 mm is obtained by die cutting.
[0131] Preparation of positive electrode:
[0132] The positive electrode active material is a ternary material composed of single crystal material and polycrystalline material, wherein the mass fraction of single crystal material in the positive electrode active material is 80%, the average particle size of single crystal material is 3.4μm, the average particle size of polycrystalline material is 10.6μm, and the average particle size of ternary material is 4.84μm. At this time, the chemical formula of the ternary material is LiNi 0.924 Co 0.057 Mn 0.019 M 0.025 O2, wherein the sum of the molar contents of element Al, element Mg and element Ti is 3476 ppm.
[0133] The positive electrode active material, polyvinylidene fluoride (PVDF), acetylene black and single-walled carbon nanotubes (CNT) are mixed in a mass ratio of 97:1.5:1.25:0.25, and a solvent N-methylpyrrolidone is added to obtain a positive electrode active slurry through a vacuum mixer; the positive electrode active slurry is uniformly coated on a high-strength aluminum foil with a thickness of 10 μm to obtain a positive electrode coating, and the coated aluminum foil is dried in a vacuum drying oven at 95° C. for 12 h, and the positive electrode sheet is rolled by a single-roll rolling machine, and a positive electrode sheet with a length of 63 mm and a width of 45 mm is obtained by die cutting.
[0134] Lithium-ion battery assembly:
[0135] (1) Lamination process:
[0136] The die-cut positive and negative electrode sheets were placed in a vacuum drying oven and baked at 90°C for 12 hours. A polyethylene film with a thickness of 8 μm was selected as the battery separator. The positive electrode sheets, separators and negative electrode sheets were stacked in sequence through a stacking machine so that the separator could separate the positive electrode sheets from the negative electrode sheets. Finally, a stacked core was obtained, in which the number of positive electrode sheets and negative electrode sheets were 22 and 23 respectively.
[0137] (2) Packaging process:
[0138] The core stack is fixed into the welding mold, the positive and negative pole ears are welded respectively, and then fixed with high-temperature tape, and finally encapsulated with an aluminum-plastic film with a thickness of 0.113 mm.
[0139] (3) Post-process:
[0140] The packaged dry battery is placed in an oven and baked at 90°C for 48 hours. After the moisture test is qualified, the electrolyte is injected, and after aging, formation, secondary sealing and sorting, a lithium-ion secondary battery is obtained. The average capacity of the battery is 3200mAh; wherein the mass content η of 2,2-difluoroethyl acetate in the electrolyte is 0.08.
[0141] Embodiment 2:
[0142] Preparation of negative electrode:
[0143] 84% artificial graphite (average particle size 8.3 μm) and 16% silicon carbon (average particle size β 10.8 μm, specific surface area γ 1.107 m 2 / g, average sphericity S is 0.848) for mechanical mixing for 5 min, and after mixing evenly, it is used as the negative electrode active material, wherein the molar content of element Si in silicon carbon is The weight content of element Si in the negative electrode active material is α=7.6%; the negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, SuperP, and single-walled carbon nanotubes are mixed in a mass ratio of 95:2:2:0.75:0.25, and an appropriate amount of water is added as a solvent. After being stirred evenly by a vacuum mixer, a negative electrode active slurry is obtained, and the negative electrode active slurry is evenly coated on the surface of a high-strength carbon-coated copper foil with a thickness of 6 μm to obtain a negative electrode coating; the coated negative electrode sheet is transferred to a vacuum drying oven and baked at 85°C for 12 hours. After the negative electrode sheet is rolled by a double-roll roller press, a negative electrode sheet with a length of 66 mm and a width of 47 mm is obtained by die cutting.
[0144] Preparation of positive electrode:
[0145] The positive electrode active material is a ternary material composed of single crystal material and polycrystalline material, wherein the mass fraction of single crystal material in the positive electrode active material is 75%, the average particle size of single crystal material is 3.6μm, the average particle size of polycrystalline material is 11.2μm, and the average particle size of ternary material is 5.5μm. At this time, the chemical formula of the ternary material is LiNi 0.865 Co 0.074 Mn 0.061 M 0.021 O2, wherein the sum of the molar contents of element Al, element Mg and element Ti is 2321 ppm;
[0146] The positive electrode active material, polyvinylidene fluoride (PVDF), acetylene black and single-walled carbon nanotubes (CNT) were mixed in a mass ratio of 97:1.5:1.25:0.25, and a solvent N-methylpyrrolidone was added to obtain a positive electrode active slurry through a vacuum mixer; the positive electrode active slurry was evenly coated on a high-strength aluminum foil with a thickness of 10 μm to obtain a positive electrode coating. The coated aluminum foil was dried in a vacuum drying oven at 95°C for 12 hours, and the positive electrode sheet was rolled by a single-roll roller press, and a positive electrode sheet with a length of 63 mm and a width of 45 mm was obtained by die cutting.
[0147] Lithium-ion battery assembly:
[0148] (1) Lamination process:
[0149] The die-cut positive and negative electrode sheets were placed in a vacuum drying oven and baked at 90°C for 12 hours. A polyethylene film with a thickness of 8 μm was selected as the battery separator. The positive electrode sheets, separators and negative electrode sheets were stacked in sequence through a stacking machine so that the separator could separate the positive electrode sheets from the negative electrode sheets. Finally, a stacked core was obtained, in which the number of positive electrode sheets and negative electrode sheets were 22 and 23 respectively.
[0150] (2) Packaging process:
[0151] The core stack is fixed into the welding mold, the positive and negative pole ears are welded respectively, and then fixed with high-temperature tape, and finally encapsulated with an aluminum-plastic film with a thickness of 0.113 mm.
[0152] (3) Post-process:
[0153] The packaged dry battery is placed in an oven and baked at 90°C for 48 hours. After the moisture test is qualified, the electrolyte is injected, and after aging, formation, secondary sealing and sorting, a lithium-ion secondary battery is obtained. The average capacity of the battery is 3200mAh; wherein the mass content η of 2,2-difluoroethyl acetate in the electrolyte is 0.05.
[0154] Embodiment 3:
[0155] Preparation of negative electrode:
[0156] 56% artificial graphite (average particle size 11.7 μm) and 44% silicon carbon (average particle size β 7.5 μm, specific surface area γ 1.292 m 2 / g, average sphericity S is 0.616) for mechanical mixing for 5 minutes, and after mixing evenly, it is used as the negative electrode active material, wherein the molar content of element Si in silicon carbon is The weight content of element Si in the negative electrode active material is α=21.17%; the negative electrode active material, sodium carboxymethyl cellulose, styrene-butadiene rubber, SuperP, and single-walled carbon nanotubes are mixed in a mass ratio of 95:2:2:0.75:0.25, and an appropriate amount of water is added as a solvent. After being stirred evenly by a vacuum mixer, a negative electrode active slurry is obtained, and the negative electrode active slurry is evenly coated on the surface of a high-strength carbon-coated copper foil with a thickness of 6 μm to obtain a negative electrode coating; the coated negative electrode sheet is transferred to a vacuum drying oven and baked at 85° C. for 12 hours. After the negative electrode sheet is rolled by a double-roll roller press, a negative electrode sheet with a length of 66 mm and a width of 47 mm is obtained by die cutting.
[0157] Preparation of positive electrode:
[0158] The positive electrode active material is a ternary material composed of single crystal material and polycrystalline material, wherein the mass fraction of single crystal material in the positive electrode active material is 85%, the average particle size of single crystal material is 3.7μm, the average particle size of polycrystalline material is 10.6μm, and the average particle size of ternary material is 4.435μm. At this time, the chemical formula of the ternary material is LiNi 0.923 Co 0.045 Mn 0.032 M 0.029 O2, wherein the sum of the molar contents of element Al, element Mg and element Ti is 4819 ppm;
[0159] The positive electrode active material, polyvinylidene fluoride (PVDF), acetylene black and single-walled carbon nanotubes (CNT) were mixed in a mass ratio of 97:1.5:1.25:0.25, and a solvent N-methylpyrrolidone was added to obtain a positive electrode active slurry through a vacuum mixer; the positive electrode active slurry was evenly coated on a high-strength aluminum foil with a thickness of 10 μm to obtain a positive electrode coating. The coated aluminum foil was dried in a vacuum drying oven at 95°C for 12 hours, and the positive electrode sheet was rolled by a single-roll roller press, and a positive electrode sheet with a length of 63 mm and a width of 45 mm was obtained by die cutting.
[0160] Lithium-ion battery assembly:
[0161] (1) Lamination process:
[0162] The die-cut positive and negative electrode sheets were placed in a vacuum drying oven and baked at 90°C for 12 hours. A polyethylene film with a thickness of 8 μm was selected as the battery separator. The positive electrode sheets, separators and negative electrode sheets were stacked in sequence through a stacking machine so that the separator could separate the positive electrode sheets from the negative electrode sheets. Finally, a stacked core was obtained, in which the number of positive electrode sheets and negative electrode sheets were 22 and 23 respectively.
[0163] (2) Packaging process:
[0164] The core stack is fixed into the welding mold, the positive and negative pole ears are welded respectively, and then fixed with high-temperature tape, and finally encapsulated with an aluminum-plastic film with a thickness of 0.113 mm.
[0165] (3) Post-process:
[0166] The packaged dry battery is placed in an oven and baked at 90°C for 48 hours. After the moisture test is qualified, the electrolyte is injected, and after aging, formation, secondary sealing and sorting, a lithium-ion secondary battery is obtained. The average capacity of the battery is 3200mAh; wherein the mass content η of 2,2-difluoroethyl acetate in the electrolyte is 0.15.
[0167] Embodiment 4 group:
[0168] This group of examples is used to verify the influence of the change in the value of "α", which is achieved by adjusting the weight content of element Si in the negative electrode active material, as follows:
[0169] Example 4a is based on Example 1, except that the negative electrode sheet and the positive electrode sheet are different, the negative electrode active material is a mixture of 99% artificial graphite and 1% silicon carbon, and the weight content of element Si in the negative electrode active material is α=0.48%. At this time, the chemical formula of the ternary material is LiNi 0.686 Co 0.096 Mn 0.218 M 0.027 O2, wherein the sum of the molar contents of element Al, element Mg and element Ti is 1865 ppm.
[0170] Example 4b is based on Example 1, except that the negative electrode sheet and the positive electrode sheet are different, the negative electrode active material is a mixture of 38% artificial graphite and 62% silicon carbon, and the weight content of element Si in the negative electrode active material is α=29.65%. At this time, the chemical formula of the ternary material is LiNi 0.929 Co 0.032 Mn 0.039 M 0.023 O2, wherein the sum of the molar contents of element Al, element Mg and element Ti is 2641 ppm.
[0171] Example 4c is based on Example 1, except that the negative electrode sheet and the positive electrode sheet are different, the negative electrode active material is a mixture of 87.5% artificial graphite and 12.5% silicon carbon, the weight content of element Si in the negative electrode active material is α=5.98%, the average particle size of the single crystal material is 4.2μm, the average particle size of the polycrystalline material is 11.3μm, the average particle size of the ternary material is 5.62μm, and the chemical formula of the ternary material is LiNi 0.825 Co 0.127 Mn 0.048 M 0.036O2, wherein the sum of the molar contents of element Al, element Mg and element Ti is 4275 ppm.
[0172] Embodiment 5 group:
[0173] This group of examples is used to verify The effect of the change is achieved by changing the content of silicon and carbon in the negative electrode active material, as follows:
[0174] Example 5a is based on Example 1, except that the negative electrode active material is a mixture of 67% artificial graphite and 33% silicon carbon. The specific surface area γ of silicon carbon material is 1.288m 2 / g.
[0175] Example 5b is based on Example 1, except that the negative electrode active material is a mixture of 74% artificial graphite and 26% silicon carbon. The specific surface area γ of silicon carbon material is 1.143m 2 / g.
[0176] Embodiment 6 group:
[0177] This group of examples is used to verify the impact of changes in the value of "k", as follows:
[0178] Example 6a is based on Example 1, except that k=0.967. In this case, the molar content x of the element Ni in the ternary material is 0.865. In this case, the chemical formula of the ternary material is LiNi 0.865 Co 0.074 Mn 0.061 M 0.021 O2, wherein the sum of the molar contents of element Al, element Mg and element Ti is 2321 ppm.
[0179] Example 6b is based on Example 1, except that k=1.041. At this time, the molar content x of the element Ni in the ternary material is 0.931. At this time, the chemical formula of the ternary material is LiNi 0.931 Co 0.031 Mn 0.038 M 0.045 O2, wherein the sum of the molar contents of element Al, element Mg and element Ti is 2584 ppm.
[0180] Embodiment 7 group:
[0181] This group of examples is used to verify the influence of the change of the average sphericity S of the silicon-carbon material, as follows:
[0182] Example 7a is based on Example 1, except that S is 0.58, and the specific surface area γ of the silicon-carbon material is 1.285 m 2 / g,
[0183] Example 7b is based on Example 1, except that S is 0.889, and the specific surface area γ of the silicon-carbon material is 1.045 m 2 / g,
[0184] Embodiment 8 group:
[0185] This group of examples is used to verify the impact of the change of "β", which is achieved by changing the average particle size of the silicon-carbon material, as follows:
[0186] Example 8a is based on Example 1, except that the average particle size β of the silicon-carbon material is 7.1 μm, and the specific surface area γ of the silicon-carbon material is 1.372 m 2 / g,
[0187] Example 8b is based on Example 1, except that the average particle size β of the silicon-carbon material is 11.9 μm, and the specific surface area γ of the silicon-carbon material is 1.038 m 2 / g,
[0188] Embodiment 9 group:
[0189] This group of examples is used to verify the influence of the change in the mass fraction r of the single crystal material in the positive electrode active material, which is achieved by adjusting the composition of the positive electrode active material, as follows:
[0190] Example 9a is based on Example 1, except that the mass fraction of the single crystal material in the positive electrode active material is 90%. At this time, the average particle size of the ternary material is 4.12 μm; the chemical formula of the ternary material is LiNi 0.925 Co 0.056 Mn 0.019 M 0.023 O2, wherein the sum of the molar contents of element Al, element Mg and element Ti is 3057 ppm.
[0191] Example 9b is based on Example 1, except that the mass fraction of the single crystal material in the positive electrode active material is 70%, and the average particle size of the ternary material is 5.56 μm; the chemical formula of the ternary material is LiNi 0.923 Co 0.057 Mn 0.02 M 0.024O2, wherein the sum of the molar contents of element Al, element Mg and element Ti is 2982 ppm.
[0192] Example 10 Group:
[0193] This group of examples is used to verify the impact of changes in the average particle size of carbon-based materials, as follows:
[0194] Example 10a is based on Example 1, except that the average particle size of the carbon-based material is 5.16 μm.
[0195] Example 10b is based on Example 1, except that the average particle size of the carbon-based material is 14.94 μm.
[0196] Embodiment 11 group:
[0197] This group of examples is used to verify the influence of the change in the mass content of 2,2-difluoroethyl acetate in the electrolyte, as follows:
[0198] In Example 11a, the mass content η of 2,2-difluoroethyl acetate in the electrolyte is 0.01.
[0199] In Example 11b, the mass content η of 2,2-difluoroethyl acetate in the electrolyte is 0.33.
[0200] In the above embodiments, the single-surface density of the negative electrode coating is 2 mg / cm 2 -10mg / cm 2 In the range of 1g / cm 3 -1.8g / cm 3 In the range of 2mAh / cm 2 -5mAh / cm 2 The single-surface density of the positive electrode coating is within 10 mg / cm 2 -20mg / cm 2 In the range of 3g / cm 3 -3.5g / cm 3 In the range of 1.77 mAh / cm 2 -5mAh / cm 2 within the range.
[0201] Comparative Example 1:
[0202] This group of comparison ratios is used to verify the impact of changes in the value of "k", as follows:
[0203] Comparative Example 1a is based on Example 1, except that k=0.923, and the molar content x of the element Ni in the ternary material is 0.825;
[0204] At this time, the chemical formula of the ternary material is LiNi 0.825 Co 0.127 Mn 0.048 M 0.036 O2, wherein the sum of the molar contents of element Al, element Mg and element Ti is 4275 ppm; the average particle size of the single crystal material is 4.2 μm, the average particle size of the polycrystalline material is 11.3 μm, and the average particle size of the ternary material is 5.62 μm.
[0205] Comparative Example 2a is based on Example 1, except that k=1.065, and the molar content x of the element Ni in the ternary material is 0.952;
[0206] At this time, the chemical formula of the ternary material is LiNi 0.952 Co 0.027 Mn 0.021 M 0.028 O2, wherein the sum of the molar contents of element Al, element Mg and element Ti is 3849 ppm; the average particle size of the single crystal material is 3.6 μm, the average particle size of the polycrystalline material is 9.2 μm, and the average particle size of the ternary material is 4.72 μm.
[0207] Comparative Example 2 Group:
[0208] This group of comparative examples is used to verify the effects of the mass content α of the element Si in the negative electrode active material, the average sphericity S and the average particle size β of the silicon-carbon material, as follows:
[0209] Comparative Example 2a is based on Example 1, except that k is 1.028, α is 14.24%, S is 0.518, At this time, the specific surface area γ of the silicon-carbon material is 1.682 m 2 / g.
[0210] Comparative Example 2b is based on Example 1, except that the negative electrode active material is a mixture of 20% artificial graphite and 80% silicon carbon, wherein k is 0.98, α is 38.1%, S is 0.967, At this time, the specific surface area γ of the silicon-carbon material is 1.023 m 2 / g.
[0211] In the above embodiment, the calculation results of the formula x=k[0.06ln(α)+1+(1-S) / 30] are shown in Table 1.
[0212] In the above embodiments, the porosity and OI value of the negative electrode coating, the ratio G of the intensity of the characteristic peak 2 at 4.1V-4.2V to the intensity of the characteristic peak 1 at 3.9V-4.1V of the DQ / DV curve of the lithium ion secondary battery containing the silicon-carbon material at the 10th charge cycle, and the relationship (L1+L3) / (L2+L4) between the intensity L1 of the first characteristic peak, the intensity L2 of the second characteristic peak, the intensity L3 of the third characteristic peak and the intensity L4 of the fourth characteristic peak in the Raman spectrum of the silicon-carbon material are recorded in Table 2.
[0213] In the above embodiments, the ratio D / E between the capacity E per unit area of the positive electrode coating and the capacity D per unit area of the negative electrode coating is in the range of 1.02-1.13.
[0214] Table 1:
[0215]
[0216] Table 2:
[0217]
[0218]
[0219] Test example:
[0220] (1) Cyclic performance test:
[0221] The batteries obtained in the embodiments of the present invention and the comparative examples were placed in a constant temperature room at 25±1°C and allowed to stand for 30 minutes. They were charged to 4.3V at a constant current of 1.8C (5760mA), and then charged to a charging current of less than 0.05C (160mAh) at a constant voltage of 4.3V. The batteries were allowed to stand for 10 minutes. The thickness of the batteries was measured by a thickness gauge. x (X = number of cycles), discharge to 2.5V at a constant current of 4C (12800mA), and let stand for 10min. The above test is a complete cycle process, and its discharge capacity (mAh) is recorded as R x (X = number of cycles), capacity retention rate U x =R x / R1×100%, change U 300 Recorded in Table 3.
[0222] (2) Confirmation of the appearance of the negative electrode after cycling:
[0223] After 300T cycles, the battery was transferred to a constant temperature room at 25±1℃ and left to stand for 30 minutes. It was charged to 4.3V at a constant current of 1.8C (5760mA), and then charged to a charging current of less than 0.05C (160mAh) at a constant voltage of 4.3V. The fully charged battery was disassembled, the negative electrode was separated, and its appearance was confirmed.
[0224] (3) Cyclic expansion rate test:
[0225] The battery obtained in the embodiment of the present invention and the comparative example is charged to 3.8V at a constant current of 1.8C, and then charged to a charging current of less than 0.05C at a constant voltage of 3.8V. After standing for 10 minutes, the battery is in a 50% SOC state. The thickness of the battery is Q0 (unit: mm) when tested by a thickness gauge. After x cycles, the battery is charged to 4.3V at a constant current of 1.8C, and then charged to a charging current of less than 0.05C at a constant voltage of 4.3V. The thickness of the battery is Q0 when the battery is removed from the stage and tested by a thickness gauge. x (Unit: mm), battery cycle expansion rate Lx = Q x / Q0×100%, L 300 Recorded in Table 3.
[0226] The performance test results of the batteries obtained in the examples of the present invention and the comparative examples are listed in Table 3.
[0227] Table 3:
[0228]
[0229]
[0230] like Figure 5 The figure shows a cross-sectional SEM image of the negative electrode sheet obtained after the battery in the present invention is fully charged and disassembled after a cycle test of 300T. It can be seen that the thickness of the SEI film on the negative electrode sheet increases, showing a certain deformation, and local black spots show lithium precipitation.
[0231] It can be seen from Table 3 that, compared with the comparative example, the lithium ion battery prepared by the present invention has no black spot lithium precipitation at the negative electrode, no diving capacity attenuation, and a low cycle expansion rate, and has good cycle performance and service life.
[0232] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A lithium ion secondary battery, characterized in that: It includes a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet includes a positive electrode active material, the negative electrode sheet includes a negative electrode active material, the positive electrode active material includes a ternary material, and the negative electrode active material includes a silicon-carbon material; The molar content of the element Ni in the ternary material is x, the average sphericity of the silicon-carbon material is S, the weight content of the element Si in the negative electrode active material is α, and x, S and α satisfy the formula x=k[0.06ln(α)+1+(1-S) / 30], 0.967≤k≤1.042, 0%<α≤30%, 0.55≤S≤0.9, x<0.95; The average particle size of the silicon-carbon material is β, 6μm≤β≤20μm; k is the coefficient.
2. The lithium ion secondary battery according to claim 1, wherein 1.004≤k≤1.033, 7.5%≤α≤21%, 0.6≤S≤0.85; And / or, 7.5μm≤β≤11μm.
3. The lithium ion secondary battery according to claim 1, wherein The ternary material includes a single crystal material and a polycrystalline material, and the mass fraction of the single crystal material in the positive electrode active material is r, 70%≤r≤90%; And / or, the average particle size of the ternary material is 2 μm-8 μm; preferably 4 μm-6 μm; And / or, the average particle size of the single crystal material is 1 μm-5 μm; And / or, the average grain size of the polycrystalline material is 8 μm-15 μm.
4. The lithium ion secondary battery according to claim 1, wherein The molar content of the element Si in the silicon-carbon material is φ, 30%≤φ≤70%; preferably, 45%≤φ≤55%.
5. The lithium ion secondary battery according to claim 1, wherein The negative electrode active material further comprises a carbon-based material, and the average particle size of the carbon-based material is 5 μm-15 μm, preferably 8 μm-12 μm.
6. The lithium ion secondary battery according to claim 1, wherein The ternary material includes a chemical formula of LiNi x Co y Mn z M a O2, M is at least one of element Al, element Zr, element Mg, element Y, element Ti, element B, element Sr, element W, element Si, element La and element Nb; and / or, 0.65≤x<0.95, 0≤y≤0.35, 0≤z≤0.35, 0≤a≤0.05; Preferably, 0.9≤x<0.95, 0.02≤y≤0.06, 0.01≤z≤0.03, 0.02≤a≤0.04; Preferably, M includes at least a combination of element Al, element Mg and element Ti, and the sum of the molar contents of the element Al, the element Mg and the element Ti is 800 ppm-8000 ppm.
7. The lithium ion secondary battery according to claim 1, wherein The negative electrode sheet further comprises a negative electrode current collector and a negative electrode coating on at least one side of the negative electrode current collector; And / or, the porosity of the negative electrode coating is C, 20%≤C≤50%; And / or, the OI value of the negative electrode coating is δ, 10%≤δ≤22%.
8. The lithium ion secondary battery according to claim 1, wherein The positive electrode sheet further comprises a positive electrode current collector and a positive electrode coating on at least one side of the positive electrode current collector, and the negative electrode sheet further comprises a negative electrode current collector and a negative electrode coating on at least one side of the negative electrode current collector; And / or, the capacity per unit area of the positive electrode coating is E, the capacity per unit area of the negative electrode coating is D, 1.02≤D / E≤1.13; preferably, 1.05≤D / E≤1.
1.
9. The lithium ion secondary battery according to claim 1, wherein In the Raman spectrum of the silicon-carbon material, at 470 cm -1 -480cm -1 The first characteristic peak is at 507cm -1 -517cm -1 There is a second characteristic peak at 1330cm -1 -1350cm -1 It has a third characteristic peak at 1590cm -1 -1610cm -1 having a fourth characteristic peak; the intensity L1 of the first characteristic peak, the intensity L2 of the second characteristic peak, the intensity L3 of the third characteristic peak and the intensity L4 of the fourth characteristic peak satisfy 0.5≤(L1+L3) / (L2+L4)≤3; And / or, the DQ / DV curve of the lithium ion secondary battery in the 10th charging cycle has a characteristic peak 1 at 3.9V-4.1V and a characteristic peak 2 at 4.1V-4.2V, and the ratio of the peak intensity of the characteristic peak 2 to the peak intensity of the characteristic peak 1 is G, 1.5≤G≤1.
8.
10. The lithium ion secondary battery according to claim 1, wherein The lithium-ion secondary battery further includes an electrolyte, wherein the electrolyte includes acetate; Preferably, the acetate comprises 2,2-difluoroethyl acetate; More preferably, the mass content of the 2,2-difluoroethyl acetate in the electrolyte is η, 0.01≤η≤0.33; further preferably, 0.05≤η≤0.15.
Citation Information
Cited By
Lithium ion battery
CN120149505A
A lithium-ion battery
CN120149505B
Lithium-ion battery
EP4819291A1